Request Strategies of Children Character in Diary of A Wimpy Kid Movie - AGUSTINA ALIDA KHOIROTUN NISA (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
Request Strategies of Children Character in Diary of A Wimpy Kid Movie Agustina Alida Khoirotun Nisa’ English Department, Faculty of Languages and Arts, Surabaya State University Agustinanisa59@yahoo.co.id Lisetyo Ariyanti English Department, Faculty of Languages and Arts, SurabayaStateUniversity Lisetyo.a@yahoo.com Abstrak Menarik untuk mendiskusikan ucapan anak-anak dalam menggunakan ungkapan permintaan dalam konteks teman sebaya dan keluarga. Anak-anak di usia ini mempunyai kemampun yang baik dalam menggunakan strategi yang berbeda dalam menyatakan permintaan. Studi ini mencoba mencari tipe-tipe apa yang dipakai anak-anak di usia sebelas tahun dalam film Diary of A Wimpy Kid dan alasan mengapa mereka menggunakannya. Dengan menggunakan metode deskriptif kualitatif, study ini menemukan bahwa anak-anak di umur sebelas tahunberhasil menggunakan ungkapan permintaan dengan benar sesuai dengan partisipan, situasi serta topiknya.Karena anak-anak di usia sebelas tahun telah mengerti tentang tindakan face-threatening, mereka bisa memilih strategi yang sesuai berdasarkan power variabel, distance, dan tingkatan imposition. Kata kunci : Kesopanan, Permintaan, Respon, Anak-anak, Keluarga, Teman Sebaya Abstract It is tempted to discuss about children utterances in using request strategy, especially in peer and family context. Children in that age have good competence in using different strategy in asking request.This study tries to find out the type of request which are used in children in the age of eleven by using Diary of A Wimpy Kid movie and the reason why they use that. By using descriptive qualitative this study has been found that children in the age of eleven is success in using request properly based on situation, topic and participant.This study says that request strategies can be displayed in children utterances. Since children in the age of eleven have understood about face-threatening act, they can choose proper type and strategy based on such variable power, distance and rating of imposition. Keywords : Politeness, Request, Response, Children, Family, Peer INTRODUCTION: In sociological side, politeness is not a choice, but rather an obligation that responsible members of society are expected to show. Politeness is the norm, and lack of politeness will likely cause problems in society and breakdowns in interactions. Request as a basic polite speech act is examined in this study. Request action is defined when someone indicates that he wants hearer to do something or refrain from doing some act. (Brown and Levinson, 1987). In daily conversation there are many ways to get the things that someone wants. They usually say to a group of friends, “Go get me that plate!”, or “shut up!” In the other hand when they are in the formal situation which contain a group of adult like parents they must say “Could you please pass me that plate, if you don’t mind?” and “I am sorry”. I don’t mean to interrupt, but I am not able to hear the speaker in the front of the room”. Different situations force people to adjust themselves, their behaviour and their words to fit the occasion. Socially it would seem unacceptable if the phrase were reversed. Many recent studies discover politeness phenomena in language usage and language context. Request is the most area which is observed because it obviously deals with face threatening act. Gender context merely describes the difference of female and male utterance in using request (Ruli, 2010).That study use found that Male tend to be direct when aexpress their need rather than Female. The thesis is from State University of Surabaya which describe the request strategies in the gender differences context. This study show the gender differences phenomena and show the women dominantly minimize face threat rather than man. Oppose to Aji’s thesis, this study do not examine gender differences in children the age of eleven. Family and peer context is emphasized in this study. Cross-cultural context dominantly explores the difference between native English and non-native English(Fukushima, 2003). Children area is alsonecessary to be explored since the certain age determines the capability of children in using request. (See further explanation in Chapter 2) Dealing with children, many linguists are more concern with their acquisition of morphology, phonology which is described more in psycholinguistic area. It deals with their competence and performance of their language development. That development happens through their early age. After they are in the middle school that are in the age between eleven until thirteen they must be good in language use and language context. The children do not get rid of their acquisition of politeness. Ervin-Trip (1977: 175) suggests that 3-year-old children begin to use variety forms to convey requests such as imperative form (Can you..), permission form (Can I..) or model embedding (You can..). Gordon and Ervin-Tripp (1984) also suggests that 4-year-old children can understand the situation e.g. ‘it goes there’ become ‘that doesn’t go there, it goes there’ which describe rule or norm oriented request and want/need statement e.g.’Mommy I need..’. Children in the age of nine until ten capable to use ‘can you’ and ‘could you’ and use request form with softening device ‘please’. As a result children in the age of eleven will perfectly recognize all request form since the acquisition of the politeness in request has been increased and improved through elementary school period. Beside language acquisition, children also learn politeness (Brown & Levinson, 1978 p.36). Politeness constitutes more than the ability to comprehend and produce particular linguistic forms. In home, children apply polite form independently with or without instruction of their parents. Home is first place in which children are exposed to social norms and language samples that represent and convey these norms is usually the family. In the family, caregivers and peers provide input for children to work on, and they also help children in socialization. It is also the important place for children to construct politeness term. In this place a naturally symmetrical power relationship between parents and children is appeared obviously.Parents teach their children how to speak with older people, how to be polite in dinner table and many other. Sometimes children learn politeness by imitating older person. Children are trying to imitate what they hear (Fromkin, Rodman, and Hyams: 2007, p.325) and have possibility to imitate what they see. Children at the early age like to mimic or imitate those adults around them that they love. Children love to please their parents then they will naturally do the same thing they do. They will be the followers of parents act and as a result parents should be careful of what kind examples which they display before their children follow that. Ladeegard (2004) argues that, according to the sex, boys and girls at that age under fifteen still have same level in acquisition of politeness. As a result this study does not display gender differences in children utterance. Children whether it is boy or girl, learn to be able to choose the proper utterance when they ask request to older people in their family. Their requests are less courteous than adults. It is not like language acquisition for example syntax and semantic that can be learned by children spontaneously. Children in acquisition of politeness routine have to be constructed with certain rules which should be taught by parents (Gleason & Perlman, 1985). Parents should take an active part explicitly instructing their children in the use of appropriate politeness device. The use of polite forms is motivated by children to sound competent (Achiba, 2003). Not only parents but also older brother or sister have a similar role to teach politeness speech act to younger, although the degree of closeness between parents and children is more intimate than their siblings. In relative power, children must be good because its must. They learn firstly in their home so that they will be ready to accept their personality in society. Peers also have a crucial rule for the children to build their communication. Like in the Diary of A Wimpy Kid movie, peers also take active part for children to develop communication system and linguistic devices. Diary of a Wimpy Kid is based on novel with same title which the first published in 2007 and was written by JeffKinney. The film was released in 2010. It tells about boy named GregHeffley and his struggles in middle school. Greg has a bestfriend named Rowley which he thinks that Rowley is too childish for boy in the age of eleven. Greg is the second son from three siblings. The relation among family member is as well as among their peers. This film tells about a middle-school boy who always stuck in bad luck. He actually wants to be a popular student the school and tries to do anything to make him become extraordinary student. Unfortunately, everything happens in the opposite way and become popular in the negative side. That is make Greg goes awry then writes all of his experience in the diary which he insists that it is journal of him. His ambition become a well-known boy in the school make him ruins his friendship with Rowley. In this movie, there are many children charactersand their utterance can be discussed. They have interaction with their peers in school and their family in their home. Children in this movie are about eleven years old who have competent in language acquisition. Since the main character in this movie is Greg who are very ambitious, arrogant and save his image, he can choose proper strategy when he wants to express his need according to situation, the addressee and weightiness of his need. In this age, children have capability to save his face and also threaten his image (see ch. 2). This study concerns with relationship between children and parents as an asymmetrical relation. In the other hand, the relationship among children and peer also sibling as a symmetrical relation. Theoritical Framework This study tells us about children pragmatic competence in this case about of politeness in request. The theory from Brown and Levinson (1987) is used to become theoretical framework in this study. They define face as self public image that everyone owns which contains positive and negative face. They (Ibid: 61) distinguish two types of face: positive and negative face. Positive face refers to the need for approval and appreciation, need to be accepted or valued by others or to be connected by others, to be treated as a member of the same group and to know that his or her wants are shared by others, while the negative face refers to the want for autonomy, freedom from imposition which not to be imposed on by others, and freedom of action which need to be independent. There are many part of politeness according to Brown and Levinson’s face-threatening act (FTAs) such as orders, requests, warnings, reminding and threats. Infact, this study discusses about request form. The requests fall into five strategies which contain bald on record, off record, negative politeness and positive face, and no FTA. There are also strategies in each types but not all of strategy is fulfilled in this study. Each strategies are provided based on the utterances which avaible in the movie. Brown and Levinson (1987:74) state that the degree of seriousness in doing FTA is based on the three factors; the social distance (D) of speaker and hearer which reflect a symmetric relation in children with their peers. Secondly is the relative power (P) of speaker and hearer which concern with an asymmetric relation in children with their parents and older brother and the third is about the absolute rating of imposition (R) in certain situation. Based on the background of the study above, the questions below will be answered. (1). What types of request are used by children character in Diary of a Wimpy Kid movie? (2). Why do children in Diary of a Wimpy Kid movie use that request strategy? Research Design and Method: This study uses descriptive qualitative.Thomas (2003) defines qualitative methods as method that involves research by describing kinds of characteristics people and events without comparing the events in term of amounts. The characters which are observed is children in the middle school (11-year-old kids). The characters in this movie dominantly use children character in peer and familtywhich suitable to conduct this study. To get an accurate data without manipulating the data, observation is needed. Several movie had to be watched and selected which one can be the most represented this study. Finally this study took Diary of A Wimpy Kid which was able to display the Request strategy in children utterance. The researcher, as an instrument of the study, watched the movie for several times to understand and got the data. Some notes which relating to the utterances about request had to be taken.After watching the movie, the scripts are searched in internet to identify the data. These scripts of the movies which had been gotten by search in internet were learned and then the children’s utterances which contain with request phenomena were taken.As the final method of collection data, the data is classified into type of the request. Analysis data technique according to Sugiyono(2011) is aimed to answer the research question in the study. After finding the utterances which related to request form, the data will be organized systematically.And the utterances which contain request form will be underlined. Participant refers to the speaker and hearer that can be disinguished as requester and requestee. Setting and scene refers to the time and place of a situation that the utterance happen. The dialogue is segmented into the type of request in order to make it easier to conduct the study. Data analysis For the first question this study take theory from the theoritical framework which concern with politeness in requesting to support the data. The children utterances which belong to request form will be identified and described whether it is bald on record, off record, negative or positive politeness, and say nothing. Second question deals with the reason why the character use the strategy. This part has to find out the background story and the motivation of the speaker to do that. This study also finds out the relationship between speaker and hearer. RESULT As the explanation of the request strategies, this study describe request into five possible types; Do the act on-record baldly (direct request). Do the act on-record with positive politeness. Do the act on-record with negative politeness. Do the act off-record (nonconventional indirect). Do not do act or no FTA (say nothing). On record On Record utterance is utterances directly addressed to another.Brown and Levinson (1987) categorize on record into two subcategorised; without redressive action or baldly (which FTA is not minimized, where face is ignored or is irrelevant) and with redressive action or baldly (which minimize face threats by implication). 1. Without redressive action Rowley: So I left my racing game at your house and Collin is sleeping over tonight so, I need it back (Diary of A Wimpy Kid, 01:19:20) Rowley adds some information to assure that his request will be accepted by the hearer. This situation Rowley as a speaker maximizes FTA and ignores negative face of the hearer which needs to be free from action and imposition. This request is categorized as request for an action. Rowley uses bald on record because he wants to threat negative face of the hearer. Rowley easily damaging Greg’s face.. It is obvious that Rowley wants to redress hearer’s face by the request which he makes in direct way. The degree of closeness and intimacy is very low since they have been argued each other. 2. With redressive action Greg : Hey I forgot my raincoat, so I’m gonna need you to walk the kids home today (Diary of A Wimpy Kid, 54:05) Speaker obviously does FTA but he tries to minimize face-threatening by adding some explanation and the reason why the speaker made that request. Itis because he has power distance over the hearer since both of them is close enough.Speaker thinks it is fine to threaten hearer’s face since hearer does not have power over the speaker and high degree of closeness. Speaker tends to express his need directly and assumes that the request will be accepted because hearer has knowledge about speaker’s condition. Greg : Mom stop dancing, you are embarassing me. Mom: Oh come on. I’m just keeping time to the music. Greg : I’m begging you, please stop it. Mom : Oh, okay (Diary of A Wimpy Kid, 01:16:00) With imperative form, the utterance is obviously threatening negative face of the hearer to make his mother really can catch the request. In the first request his mother ignores him and keeps dancing. Then he continues to give additional expression with mitigation aspect which provide softening deviceto make the request appears less threaten and more polite.He is in the embarrassing situation. Bald on record is used when speaker has consciously chosen to be maximally offensive. Although the relationship between them is mother and her son which imply high power relation, in this situation this factor is avoided. High rating of imposition becomes main factor in this situation. Greg uses that to assure hearer that Greg as speaker truly wants his other receive the request. Positive politeness 1. By using in group identity markers Speaker can use address form, jargon or slang to mention something but speaker and hearer have known about it. Fregley : Hey guys wanna see my secret freckels? (Diary of A Wimpy Kid, 08:41) Fregley in this situation minimizes face threat and satisfies the hearer’s positive face. He also emphasizes closeness and intimacy between speaker and hearer. He tries to convey in-group membership by saying “hey guys”. Fregley as a speaker, who is still just friend like other, wants to show that he wants to be part of them. It is because he wants to look familiar and implies that he want to be accepted in that group. Since the relationship between speaker and hearer is friend with lack of likeness degree. 2.By asserting or presupposing speaker’s knowledge, and concern for hearer’s wants Speaker states the utterances which want to presuppose that speaker’s want would become hearer’s want also. Angie : You know, I really like your point of view, you should sign up to the school paper. (Diary of A Wimpy Kid, 24:29) With declarative form,Anggie as a speaker redresses directed toward positive face of hearer which need to be respected, accepted and approved. Speaker’s want thought be desirable for hearer too. This request does not threatening hearer’s face if speaker wants to show his desire to make hearer to do something for speaker. Anggie uses that strategy because she wants to put pressure on Greg to cooperate with her. It is also to imply knowledge of hearer’s wants and willingness to fit one’s own wants with them. Since the relationship between them is a girl with a boy with getting knows her name, Anggie tries to emphasize their intimacy and shows that both of them have similar interest in school paper. 3.By including both speaker and hearer in the activity Speaker conveys their closeness and intimacy by using some expression. This solidarity strategy will be marked via inclusive terms such as ‘we’ and ‘let’s’ to invite hearer in activity together. Greg : Oh man, this one, we burn. (Diary of A Wimpy Kid, 35:05) Although the utterance indicates direct request, but the expression “oh man” and “we” emphasizes equality between them. Positive politeness strategy is oriented toward the positive face of the hearer which has desire to be approved as a member in a group. It also minimizes FTA by assuring the hearer that speaker consider himself to be ‘of the same kind’ that hearer also wants speaker’s want.Greg uses this strategy because he wants to satisfy positive face of the hearer. The word “we” in this situation actually does not mean ‘you’ and ‘i’ which just include speaker in the activity. Since relationship between them is best friend, stressing closeness suitable to be applied. Speaker treats the hearer as a member of an in-group, a friend. 4.By asking for reasons Speaker asks the reason why hearers do not do based on what speaker wants to ask to the hearer. Greg : You know what, if you like it so much, then Why don’t you go do it yourself? (Diary of A Wimpy Kid, 53:32) Actually this situation leads to pressure to go off record, to test hearer and see if he is cooperative. If hearer is likely cooperative enough, the context may be enough to push the off-record reason into an on-record request. Since positive politeness is in the indirect request area, FTA is minimized and tries to satisfy hearer positive politeness which wants to be appreciated and approved. It is because Greg as a speaker assume that Rowley as a hearer wants speaker’s want. Indirect suggestion is actually demanded rather than give the reason. Since the relationship between speaker and hearer is friendship, power distance between them is high enough. Speaker is trying to be indirect to save hearer’s face and does not damage speaker’s face. Negative Politeness Negative politeness strategies refer to the use of conventional indirectness or please to maximize the hearer’s freedom of actions (Brown Levinson, 1978). It is oriented mainly toward partially satisfying (redressing) hearer’s negative face, his basic want to maintain claims of territory and self-determination. There are four strategy which is provided in this study. 1. By being conventionally indirect By being conventionally indirect degrees of politeness in the expression of indirect speech acts. Rowley : Can I throw at you now? Greg : Later. You’re better at riding than I am, and I’m a better thrower. (Diary of A Wimpy Kid, 28:12) Rowley as a speaker tries to minimize FTA. As a result face-saving aspect is dominantly used in the situation. Speaker explicitly formulates a question, and, by implication, intends that question to be taken as a requestSince Rowley wants to be a thrower he uses negative politeness because there is a big possibility for speaker to refuse the request. This strategy gives redress to hearer’s negative face by explicitly expressing doubt “can I..”. Rowley tries to avoid face damage because of hearer’s refusal although he tries to convey his want. The relationship between them is best friend. So each other do not have power to emphasize their need directly in this situation. 2. By questioning or hedging Speaker can show his feeling about he has not taking full responsibility for the truth of his expression. Questioning or hedging can also show strengthen face of threatening act of speaker. Greg : Don’t you ever say “hi” or “hello” before you start talking? (Diary of A Wimpy Kid, 24:08) The utterance is not directly addressed to the hearer. This type helps speaker to avoid responsibility of doing FTA when speaker actually wants to do FTA but wants to be indirect also.Greg uses the strategy because he actually feels uncomfortable and asks question like that to make Anggie realizes that he does not like her. The utterance could be glossed as “I indirectly ask request to you to say ‘hi’ or ‘hello’ before interrupting us”. Since the relationship between speaker and hearer is a boy with a girl who ‘just getting know her name’, they have lack of closeness degree. Greg tends to be indirect since power of distance between them is low. 3. By being pessimistic Speaker is not sure with what s/he wants to ask for and this strategy expresses asking permission to make request. This strategy describes that speaker asks request to hearer indirectly to do a particular act by questioning hearer’s ability to do that act (can you). Greg : Mom, can you tell him to stop calling me like that? How if somebody hears? (Diary of A Wimpy Kid, 39:13) Negative politeness eliminates FTA and emphasizes face-saving aspect. Speaker tends to save hearer’s negative face which has a right and autonomy to be free from action and imposition. Since relationship between them is a son with his mother, asymmetrical relation is emphasized. As a vertical relationship, the power of mother is higher than her son. Greg avoid direct request like an assertion “I’d like you to tell him stop calling me like that” because he has to save hearer’s face who has power over him. The speaker wants to communicate his desire to be indirect even though in fact the utterance goes in direct. 4.By going on record as incurring a debt, or as not indebting hearer Speaker actually wants to ask request in direct way. But to make the request less threaten they use some additional expression. Greg : Now if you’ll excuse me, I need to secure the perimeter. (Diary of A Wimpy Kid, 47:30) With declarative form, Greg as a speaker wants to be direct but in indirect way, since this utterance tends to be conventional indirect. This utterance also belongs to request for permission because speaker does not ask hearer to do something but ask her to permit speaker to do something. Greg uses this strategy because Greg is trying to preserve his face and also satisfy hearer’s face wants. He wants to save Anggie’s face as a redress. This strategy is suitable to be applied since the relationship between hearers and speaker is friend which has low degree of degree. The more distant someone, the more indirect the utterance he made. Off Record Off record which belongs to nonconventional indirect make speaker less threaten hearer’s face. 1. By giving hints Speaker provides some hints that consist in ‘raising the issue of’ some desire to do something, say, stating motives or reasons for doing action. Quentin : What did he just say to you? Greg : Oh, I think my ride is here (Diary of A Wimpy Kid, 16:44) The utterance is not directly addressed to the hearer. This type helps speaker to avoid responsibility of doing FTA when speaker actually wants to do FTA. Speaker decides to say something, he does not have to ask for anything. It is because he wants to evade the responsibility of damaging hearer’s face by leaving the option for hearer to interpret that as off record requests. Since the relationship between speaker and hearer is a boy with someone who ‘just know the name’ as the result Greg with low degree of closeness to do FTA or even FSA (Face-saving act). 2. By being overstate Speaker tends to says more than is necessary. He delivers the utterance by exaggerating or choosing a point on a scale which is higher than the actual state of affairs. This strategy can be found in this movie when speaker use “I’ve told you like a billion times” when actually speaker does not say that in billion times. Greg : ‘Play’ rowley, ‘play’? I’ve told you like a billion times that the guys in our age say “hang out”, not “play” (Diary of A Wimpy Kid, 17:30) This declarative form is used when speaker wants to do an FTA but in indirect way. Speaker threatens Rowley’s negative face implicitly. If a speaker wants to do it off record and leave it up to the addressee to decide how to interpret the utterance. Speakersays something which higher than actual state. It is just implicature that he has been told hearer for many times. Rowley as a hearer is expected to understand what speaker wants to ask. Since relationship between them is friendship, the message can easy to be understood and Greg as a speaker does not get trouble if he threatens his friend’s negative face and damages his positive face. No FTA No FTA or say nothing is type of request which explain that nothing is said. It is because the risk of face loss is extremely great (Yule: 1997). No FTA indicates performing no face-threatening acts. There are two strategies in this type; when speaker provvide hints and when speaker shows his mimic. 1.Hint in this situation, when they want to express their need, speakers says nothing but the provide a hint. Greg and Rowley : (Stands and brings tray) Bryce : That seats is saved. (Diary of A Wimpy Kid, 15:45) Actually they want to sit in the table like other student. But they are afraid. As a result they just stand there and expect their friends understand that Greg and Rowley want to sitthere. Speaker rejects to do FTA by saying nothing. Speaker does not threaten hearer’s FTA or damages them. Greg also does not use face-saving aspect in their action. It is because the risk of face loss is extremely great. Nothing is said makes the speaker seems to prefer to have their needs recognized by the other without having to express those needs in language. Since relationship between them is boywith someone who get to know their name. Solicitousness is expected to be gotten by Greg who needs to sit at same table. 2.Mimic Without any verbally request, speaker can just show his mimic. Rowley : Oh, Greg is only here because he really wants to be something... Greg : Rowley!! Rowley : (silent) (Diary of A Wimpy Kid, 24:15) He tries to avoid face-threatening act by saying nothing. However he hopes that Rowley agrees with Greg to shut up.Since the relationship between them as close friend, their intimacy makes the communication can be easily understood to one another. Greg provides a hint by calling hearer’s name to make hearer feel conscious with that request. Nothing is said make the risk of face loss is extremely great. Those analysis are summarized into table which contain the request utterances, the type and the strategy. No. Request Utterances Type Strategy 1 So I left my racing game at your house and Collin is sleeping over tonight so, I need it back On record Without Redressive Action 2. Hey, I forgot my raincoat, so I’m gonna need you to walk the kids home today On record With Redressve Action 3. Mom stop dancing, you are embarrassing me. I’m begging you, please stop it. On record Withhout & With Redressive action 4. Hey guys, wanna see my secret freckels? Positive Politeness By using in group identity markers 5. You know, I really like your point of view, you should sign up to the school paper Positive Politeness By asserting or presupposing speaker’s knowledge, and concern for hearer’s wants 6. Oh man this one, we burn. Positive Politeness By including both speaker and hearer in the activity 7. Why don’t you go do it yourself? Negative Politeness Asking the reason 8. Can I throw at you now? Negative Politeness Conventionally indirect 9. Don’t you ever say ‘hi’ or ‘hello’ before you start talking? Negative Politeness By questioning 10 We should probably do something outside Nwgative Politeness By Hedging 11 Mom, can you tell him to stop calling me like that? Negative Politeness Bybeing pessimistic. 12 Now if you’ll excuse me, I need to secure the perimeter. Nrgative Politeness By going on record as incurring a debt. 13 Oh, I think my ride is here Off-record Giving hint 14 I’ve told you like a billion times that the guys in our age say “hang out”, not “play” Off- record Overstate 15 Rowley!! No-FTA Mimic 16 (Stand and bring tray) No-FTA .Hint Table 1: Request Utterances Context situation, participant, setting, and topic are basic factors that influence the children character using the type of request itself. Participants include who is asking and who is s/he asking to. It refers to variable which include in the dialogue (Age, distance). The setting of the interaction includes when and where they are speaking. The topic means what is being talked. Setting concerns with the third variable which include rating of imposition. Children in the age of eleven can differentiate their language usage based on who requestee is. Since the requestee is friend who was same age, they tend to satisfy hearer face by using positive politeness. They also still maximize FTA since hearer does not need to be respected. In the other hand when the requestee is older than them or with requestee with low degree of closeness they tend to respect them by being indirect and minimizing FTA. It is appeared when children try to imply they want, they tend to use negative politeness and on record but with mitigating device. Children in this movie can use certain request strategy based on the topic which being talked by them. Topic deals with the rating of imposition that requester may indirectly or directly asks request based on what they want to ask. The more burden which want to express, the more indirect the request is uttered. Situation holds an important role in the use of request strategy. When in danger or urgent situation, requester does not have to minimize FTA or be indirect. It is because the ambiguity or unambiguous in the communication can happen. As a result clear, direct and fast response is needed to make requestee responds and catches the message fast. Children in this movie can successfully minimize the FTA by using certain request strategy which is reflected in the language usage. Greg tends to be direct, and Rowley as his friends tends to be indirect. Since Greg is a reflection of ambitious, bossy and arrogant boy and Rowley is a childish, innocent and caring heart. DISCUSSION: It is tempted to interpret that this study finds that children in the age of eleven use all of types in the request succesfully. It is more likely that the data reported tells something about children pragmatic’s competence and their awareness of applying sociolingusitics area. According to Ladeegard, there is not gender differences of children in the age of 3 until 7. Not only boys but also gilrls, use same umitigated and/or mitigated device in their utterances. This statement is confirmed in this study. Although the children’s utterances which are analysed through this film is a boy, this study can speculate that girl also have similar degree in using those types of request, which also inlclude mitigated and umitigated device. The three varibles including power, distance and rating of imposition influence the choice in requesting and responding strategies between children and their requestee. These result support Brown and Levinson’s claim that their three variables are crucial in determining the choice of politeness strategies which is used in request strategies, especially in family and peer context. Since the children grow up, they also learn how to express their want more proper by the time they get older. As Ervin-Tripp has said that (in Ch. 1) children in the age nine until ten they can differentiate the using ‘can you’ and ‘could you’. They also has used ‘please’ to soften their request. This may indicate that children in the age of eleven is the perfect age to be expert in using request strategies according to situation, participant and topic. And it is obviously proven in this study when the children in the age of eleven are succesfully accomplished their request in six different types according to theory of Brown and Levinson’s politeness with various situations, participants and topics. According to Ladeggard (2003; 2018)argues that “Children have a high degree of pragmatic competence because they know the contextual norms of the public context where peer group influence is the predominant force of children’s play and interaction and where assertive behaviour, not politeness is being rewarded” That statement is confirmed in this study since children in the age of eleven are able to use request strategies properly when they are with their peer. Ladeegard (2003; 2019) also speculates that “They are aware of a different set of norms applying to the home context where, pressummably, parents will expect their children to act politely and consequently reward them when they do” From his speculation, it has been proven in this study since children in the age of eleven also are able to be indirect when they are with their parents. It is because in the age of eleven children has capabilty to apply social norm not only in their peer group but also with their family. Direct request form has been uttered by children when the requestee is their peer and their sibling. When they are with their parent, they tend to be indirect by using negative politeness. They even use on record as a direct request but with mitigating device ‘please’ to soften hs utterance. CONCLUSION: There are two statements of the problem n this study. The first statement of the problem is about the type of the request which is used by children in Diary of A Wimpy Kid. This problem is answered with using Brown and Levinson’s theory. Based on Ervin-Trip’s theory which state that children in the age ten can differentiate the using “can you” and “could you” , this study finds that in the age of eleven children must be able to use request strategy in different types. This study do not differentiate the children based on their gender. Because based on Ladeegard (2003), there is not gender difference in using language when they are still under twelve. Parents use similar way to teach them how to express their need. By using 16 data utterances, this study shows that children have capability to use request strategy based on context, especially in peer and family context. Six types of request which is provided in this study based on Brown Levinson’s theory have been accomplished by children in the Diary of A Wimpy Kid movie. Five types includes on record, off record, negative politeness, positive politeness, and no FTA. Children are able to do FTA whether maximise or minimise face-threatening aspect. Children also have capability to do face-saving act since they want to satisfy hearer’s face by their request. The next statement, after analysing the type, the reason children in this movie use that strategy is found. This statement is also answered by giving strategy in every type of the request based on Brown and Levinson’s theory. It is assumed that children in the age are able to show different strategy consider to the person whom he is talking to the topic, the situation, the ways of making request (including intonation) and the choose the right types of request when they perform the request. Children who produce request must pay attention with those considerations, in order to maintain a good relationship with other participant unless it would be assumed as rudeness, sarcasm or even joking since the hearer completely misinterprets the given message. Suggestion: It is suggested that children in the age of eleven are capable to acquire the strategy of request. Parents who have children in the age of eleven must be aware of this age since children can misused the strategy if parents do not give good instruction to them. Teachers in this school also take an imprtant role to give good example so that the children can imitate what they hear and what they see from the teacher. Hopefully, this study can help the student of linguistic, who are interested to investigate further about request strategy. However, it is realized that this study only shows children in the age of eleven phenomena in using request only in peer and family context. References: Achiba, M.(2003).Learning to Request in a Second Language. Cromwell Press Ltd: Great Britain. Aji, Ruli. (2010). The Request Strategy Used by The main Character in AntonChekov’s the Boor. StateUniversity of Surabaya (unpublised) Al-Marrani, Yahya M Ali &AzimahBintiSazalie. (2010) Polite Request Strategies by Male Speakers of Yemeni Arabic in Male-Male Interaction and Male-Female Interaction. Penang,1327-774x. University Sains Malaysia.The international Journal of Language Society and Culture. Brown, P.&Levinson, S.C. (1987). Politeness: Some Universalsin Language Usage. Cambridge: CambridgeUniversityPress. Ervin-Tripp, S. (1977). Wait for me, roller-skate. In C. Mitchell-Kernan& S. Ervin-Tripp (Eds.), Child discourse. New York:Academic Press. Fromkin, Victoria., Rodman, Robert., &Hyams, Nina. (2009). An Introduction to Language (9th edition).Wadsworth, Cengage Learning. USA. Fukushima, Saeko. (2003). “Request and culture: Politeness in British English and Japanese.” European Academic Publisher.Germany. Gleason, JeanBerko. Perlman. RivkaV.,(1985). Acquiring Social Variation in Speech.In: Giles. Howard, Clair, RobertN. St (Eds), Recent Advances in Language, Communication and Social Psychology. Erbaum.London. Holmes, J. (1992). An Introduction to Sociolinguistic, New York: AddisonWesley. Longman Ladegaard, HansJ.(2004).Politeness in Young children’s speech: context, peer group infuence and pragmatic competence. Journal of Pragmatics, 36,2003-2022 Sugiyono.(2011). MetodePenelitianKombinasi (Mixed Methods).Bandung. Penerbit Alfabeta. Thomas, R.Murray. (2003). Blending Qualitative& Quantitative:Research Method in Theses and Dissertation. Corwin Press: California. Yule, George. (1997). Pragmatics.Oxford University Press.